The marriage buyout : the troubled trajectory of U.S. alimony law - Starnes, Cynthia (New York : New York University Press, 2016)
From divorce court to popular culture, alimony is a dirty word. Unpopular and rarely ordered, the awards are frequently inconsistent and unpredictable. The institution itself is often viewed as an historical relic that harkens back to a gendered past in which women lacked the economic independence to free themselves from economic support by their spouses. In short, critics of alimony claim it has no place in contemporary visions of marriage as a partnership of equals. But this book argues that alimony is often the only practical tool for ensuring that divorce does not treat today's primary caregivers as if they were suckers.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 1, 2016).
Keywords: Alimony -- United States; Alimony -- Economic aspects -- United States; Alimony -- Social aspects -- United States; Law; United States of America, USA; Family law: marriage, separation & divorce